FENOMENA BELANJA ONLINE : KASUS PENGGUNA FITUR SHOPEE PAYLATER: Studi Kasus pada 4 Mahasiswa Pendidikan Sosiologi Universitas Negeri Jakarta 2020 - ; Natasya Diva Naomi (Saskara : Indonesian Journal of Society Studies, 2022)
Online shopping is a process of buying goods or services from store who sell goods or services via the internet. In this procedure, the goods being traded are offered through displays with pictures on a website or virtual shop. Online shop is one of the impacts of technological developments. The skyrocketing use of online shops and their various features that pamper consumers has created a tendency for people get everything they want or need more practical. This study tries to explore consumption actions carried out by students who use one of the online shop features, namely the Shopee Paylater payment system. The act of consumption becomes a lifestyle and social construction that is packaged in an economic activity. The consumption action taken is also related to rationality which refers to the effectiveness of shopping.